Global and local constitutive behaviors of friction stir welded AA2024 joints. Issue 9 (September 2017) - Niu, Pengliang; Li, Wenya; Zhang, Zhihan; Yang, Xiawei
Abstract: In this study, the global and local tensile properties of friction stir welded AA2024 joints were measured with the aid of digital image correlation (DIC) method. A novel model was proposed to describe the global and local constitutive behavior of the joints based on DIC data. Different from conventional division of the zones across the joints, a new reasonable division was proposed, i.e. four zones including central low hardness zone (CLHZ), first heat affected zone (HAZ-I) close to TMAZ, second heat affected zone (HAZ-II) close to base metal (BM) and BM in term of the characteristic distribution of hardness. Results reveal that local true stress-true strain curves are different in each zone of interest. Plastic deformation of the joints is concentrated in CLHZ, where the lowest yield stress and the largest strain appear. Therefore, strain localization and necking occur here in a sequence. In addition, the global true stress-true strain curves and yield stresses at various ratios of the width of CLHZ zone to the gauge length are accurately predicted using the proposed constitutive model of the joints.